Trade relations between the Khiva khanate under Shaibanid dynasty and England - Jahongir Razzakov (Global Scientific Publishing, 2024)
In this article gives information about how During the Shaibanid dynasty, the Khanate of Khiva experienced a significant increase in trade relations, establishing strong partnerships with neighboring countries such as Iran, Russia, Afghanistan, and the Emirate of Bukhara. The British Empire also sought to cultivate consistent trade ties with the Khanate of Khiva during this period. In the 16th century, British records on Central Asia provided comprehensive insights into the region’s geography, borders, trade commodities, and particularly focused on the transit areas of the Khanates of Bukhara and Khiva. As European merchants faced challenges trading with Eastern countries via the Mediterranean Sea due to Ottoman control, the northeastern route through Central Asia became vital for British trade connections with Eastern nations
Keywords: Khanate of Khiva; Kaspian trade; English merchants trade routes